Proza Bohumila Hrabala w polskich przekładach (w przestrzeni między „hospodską historką” a gawędą szlachecką) - Soliński, Wojciech (Zagadnienia Rodzajów Literackich, 2019)
One of the basic tasks that is expected of artistic translation is the preservation of — as far as it is possible — the original genre structure of the source text in the target text. This paper attempts to address the question how this task is being accomplished in the translation of long and short prose forms by the Czech author Bohumil Hrabal, including causiere, črta, esej, efemera, montaž, novela, povídka, reflexe, skica. It may seem that the publication of several compendia related to his literary heritage, that is, Slovník Bohumila Hrabala or Czesko-polski słownik terminów literackich by Baluch and Gierowski should help in genological ordering of Polish translations of Hrabal’s works, affect the translation of texts that have not been rendered into Polish yet, and enable correct genological classification of texts that have already been translated. The author’s ambition is to find the answer to the question of whether such genological ordering is actually possible.